Inhibitory effects of pentacyclic triterpenoids from Astilbe rivularis on TGFBIp-induced inflammatory responses in vitro and in vivo. (25th July 2016) - Jung, Byeongjin; Chung, Jiwoo; Zhou, Wei; Lee, Taeho; Na, MinKyun; Bae, Jong-Sup
Abstract: Transforming growth factor β induced protein (TGFBIp) is an extracellular matrix protein which expression in several cell types is greatly increased by TGF-β. TGFBIp is released by human umbilical vein endothelial cells (HUVECs), and functions as a mediator of experimental sepsis. Pentacyclic triterpenoids bearing a carboxyl group at C-27 position, 3β, 6α-dihydroxyolup-20(29)-ene (1 ), 3β, 6β-dihydroxyolean-12-en-27-oic acid (2 ) and 3β, 24-dihydroxyolean-12-en-27-oic acid (3 ), are representative bioactive molecules in the genus Astilbe that possess cytotoxic, anti-inflammatory and wounds healing activities. Based on the biological effects of C-27 carboxylated pentacyclic triterpenoids, we investigated the anti-inflammatory effects of compounds1–3 against TGFBIp-mediated vascular inflammatory responses. The anti-inflammatory activities of compounds1–3 were determined by measuring permeability, leukocytes adhesion and migration, and activation of pro-inflammatory proteins in TGFBIp-activated human HUVECs and mice. We found that compounds1–3 inhibited TGFBIp-induced barrier disruption, expression of cell adhesion molecules (CAMs) and adhesion/transendothelial migration of neutrophils to human endothelial cells. Each compound also suppressed TGFBIp-induced hyperpermeability and leukocyte migration in vivo . These results suggest that compounds1–3 possess anti-inflammatory functions by inhibiting hyperpermeability, expression of CAMs, and adhesion and migration of leukocytes, thereby endorsing its usefulness as a therapy for vascular inflammatory diseases. Highlights: Transforming growth factor β induced protein (TGFBIp) is an important extracellular mediator of sepsis. Compounds1–3 inhibited LPS-induced secretion of TGFBIp. Compounds1–3 inhibited TGFBIp-mediated hyperpermeability. Compounds1–3 inhibited TGFBIp-mediated septic response. Compounds1–3 reduced TGFBIp-induced septic mortality.